2018
DOI: 10.1002/qj.3201
|View full text |Cite
|
Sign up to set email alerts
|

Role of moisture patterns in the backbuilding formation of HyMeX IOP13 heavy precipitation systems

Abstract: International audienceMediterranean regions are regularly affected by heavy convective precipitation. During the Hydrological Cycle in the Mediterranean Experiment Intensive Observation Period 13 (HyMeX-IOP13), the multi-platform observation strategy allowed analysing the backbuilding convective systems which developed on 14 October 2012 as well as the associated moisture structures in the environment upstream of convection.The numerical simulation at 2.5-km horizontal resolution succeeds in reproducing the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 48 publications
0
40
1
Order By: Relevance
“…Meteorol. Soc ., .) and described to a lesser extent in Barthlott and Davolio (2016) and Rainaud et al (2016).…”
Section: Case‐studiesmentioning
confidence: 96%
“…Meteorol. Soc ., .) and described to a lesser extent in Barthlott and Davolio (2016) and Rainaud et al (2016).…”
Section: Case‐studiesmentioning
confidence: 96%
“…Schumacher and Johnson () examined the organization and environmental properties of extreme‐rain‐producing MCSs in the United States over a 3‐year period and showed that extreme local rainfall is often associated with back‐building/quasi‐stationary MCSs, which occur when new convective cells repeatedly form upstream of their predecessors and pass over a particular area. The continuous development of upstream convection requires triggering factors, for example, frontal lifting (Schumacher et al, ), outflow boundaries (Houston & Wilhelmson, ; Houze, ; Jeong et al, ; Schumacher, ; Schumacher & Peters, ; Wang et al, ), interaction between the low‐level jet and the midlevel circulation (mesoscale convective vortices; Schumacher, ; Schumacher & Johnson, , ), orographic lifting (Duffourg et al, ; Soderholm et al, ), and thermodynamic effects associated with latent heating/cooling (Wang et al, ). Schumacher and Johnson () also indicated that back‐building/quasi‐stationary MCSs are more dependent on mesoscale and storm‐scale processes, particularly lifting provided by cold outflows from previous convection, than on preexisting synoptic boundaries.…”
Section: Analysis Of Key Factors For the Heavy Rainfallmentioning
confidence: 99%
“…Jaussaume et al, 1984;Sturm et al, 2005;Blossey et al, 2010). COSMOiso has already shown its capability to simulate the variations of stable water isotopes at the event timescale Aemisegger et al, 2015) as well as in a climatological context (Christner et al, 2018;Dütsch et al, 2018). It includes two additional parallel water cycles for each of the heavy isotopes (H 18 2 O, HD 16 O), which are applied only diagnostically and do not influence other components.…”
Section: Cosmoiso Model Configuration and Simulationmentioning
confidence: 99%
“…In this favourable large-scale situation, organized deep convection can occur and often produces highimpact events, with rainfall amounts larger than 100 mm in less than 6 h. The origin of the moisture feeding the convective systems is an important research topic that has been addressed using different techniques and tools, such as trajectory and numerical tracer analyses (e.g. Turato et al 2004;Winschall et al, 2012;Duffourg and Ducrocq, 2013;Winschall et al, 2014;Röhner et al, 2016;Duffourg et al, 2018;Lee et al, 2018). These studies found substantial contributions of subtropical and tropical moisture coming from various sources such as Africa (latitude ≥ 20 • N) and the extratropical remnants of Atlantic tropical cyclones, among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation